Dampak Sosial dari Penerapan Konsep Go Green pada Greenhost Boutique Hotel Yogyakarta - Elisabeth Fifi Siswanti; Nur Widiyanto; Kiki Rizki Makiya (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the social impact of the Go Green concept implemented at Greenhost Boutique Hotel Yogyakarta using the Global Sustainable Tourism Council (GSTC) indicators. A qualitative descriptive approach was applied through interviews, observations, and documentation involving hotel management, employees, local community members, and small business owners. The findings reveal that Greenhost’s sustainability practices not only focus on environmental efficiency but also emphasize community empowerment, inclusive employment, and cultural preservation. The hotel creates significant social value by supporting local micro and small enterprises (MSMEs), providing job opportunities for local residents, and collaborating with artists to promote cultural identity. These initiatives foster strong social cohesion and mutual benefits between the hotel and the surrounding community. The results contribute to understanding how socially driven sustainability practices can enhance destination resilience and provide a model for other hotels seeking to implement the GSTC framework effectively.